2007
DOI: 10.1126/science.1140818
|View full text |Cite
|
Sign up to set email alerts
|

Noise in Gene Expression Determines Cell Fate in Bacillus subtilis

Abstract: Random cell-to-cell variations in gene expression within an isogenic population can lead to transitions between alternative states of gene expression. Little is known about how these variations (noise) in natural systems affect such transitions. In Bacillus subtilis, noise in ComK, the protein that regulates competence for DNA uptake, is thought to cause cells to transition to the competent state in which genes encoding DNA uptake proteins are expressed. We demonstrate that noise in comK expression selects cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
637
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 616 publications
(657 citation statements)
references
References 30 publications
18
637
0
2
Order By: Relevance
“…The cells protect themselves by suspending growth. Further examples where a similar strategy has been observed include various bacteria (Maamar et al 2007;Süel et al 2007), the yeast prion (True and Lindquist 2000) and viruses (Stumpf et al 2002).…”
Section: Introductionmentioning
confidence: 80%
“…The cells protect themselves by suspending growth. Further examples where a similar strategy has been observed include various bacteria (Maamar et al 2007;Süel et al 2007), the yeast prion (True and Lindquist 2000) and viruses (Stumpf et al 2002).…”
Section: Introductionmentioning
confidence: 80%
“…Recent experiments using molecular biology methods (such as those incorporating green fluorescent protein expression under the lacoperon promoter) permitted to confirm and further study the region of bi-stability of the lac-operon even when multiple input variables (TMG that acts as the inducer and glucose, for example) were used [32]. Furthermore, multi-stable gene expression and phenotype switching in varying environmental conditions have been well documented in many natural and artificially constructed biological systems [39,27,17,37,42,34,29,20,13,16,33]. These experiments were complemented by a substantial body of theoretical work that demonstrated that organisms can gain fitness by adjusting the rate of switching between phenotypes, or switching thresholds, to the law of environmental variations.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance fitness in such environments, identical cells in isogenic populations have the capacity to stochastically differentiate into various phenotypes with special attributes (1)(2)(3)(4)(5)(6)(7)(8)(9). Stochastic fate determination guarantees variability because it provides each cell with the freedom to choose its own fate.…”
mentioning
confidence: 99%
“…This hedge survival strategy allows the population to continuously deploy specialized cells in anticipation of possible drastic changes in conditions. Canonical examples include transitions into competence (2)(3)(4)(5)(6)(7)(8)(9) and transitions into slow-growing persister cells (7,10). Interestingly, although each cell has the freedom to determine its own fate, the ratio between the phenotypes is adjusted to fit the encountered and anticipated conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation